AtSEC22 Regulates Cell Morphogenesis via Affecting Cytoskeleton Organization and Stabilities - Guan, Li; Yang, Shurui; Li, Shenglin; Liu, Yu; Liu, Yuqi; Yang, Yi; Qin, Guochen; Wang, Haihai; Wu, Tao; Wang, Zhigang; Feng, Xianzhong; Wu, Yongrui; et al. (Frontiers in Plant Science, 2021)
The plant cytoskeleton forms a stereoscopic network that regulates cell morphogenesis. The cytoskeleton also provides tracks for trafficking of vesicles to the target membranes and fusion with them by SNARE proteins. The vesicle-SNARE, Sec22, regulates membrane trafficking between the ER and Golgi in yeast and mammals. Arabidopsis AtSEC22 might also regulate early secretion and is essential for gametophyte development. However, the role of AtSEC22 in plant development is unclear. To clarify the role of AtSEC22 in the regulation of plant development, we isolated an AtSEC22 knock-down mutant, atsec22-4, and found that cell morphogenesis and development were seriously disturbed. atsec22-4 exhibited shorter primary roots, dwarf plants, and partial abortion. More interestingly, the atsec22-4 mutant had less trichomes with altered morphology, irregular stomata, and pavement cells, suggesting that cell morphogenesis was perturbed. Further analyses revealed that in atsec22-4, vesicle trafficking was blocked, resulting in the trapping of proteins in the ER, collapse of structures of the ER and Golgi apparatus. Furthermore, AtSEC22 defects resulted in impaired organization and stability of the cytoskeleton in atsec22-4. Our findings revealed essential roles of AtSEC22 in membrane trafficking and cytoskeleton dynamics during plant development.